2014
DOI: 10.1017/s0033291714000282
|View full text |Cite|
|
Sign up to set email alerts
|

Reappraising the long-term course and outcome of psychotic disorders: the AESOP-10 study

Abstract: Background-Studies of the long-term course and outcome of psychoses tend to focus on cohorts of prevalent cases. Such studies bias samples toward those with poor outcomes, which may distort our understanding of prognosis. Long-term follow-up studies of epidemiologically robust first-episode samples are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
212
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(235 citation statements)
references
References 35 publications
21
212
2
Order By: Relevance
“…We used this measure at the end of the follow-up period to obtain standardised retrospective assessments of patients' experiences, clinical and social outcomes for the entire period of illness operationalised as the period from the first contact with mental health services for FEP to the date of the last assessment recorded in electronic notes. The LCS measure has been widely used in prospective and retrospective studies (Ajnakina et al, 2017;Morgan et al, 2014;Schoeler et al, 2017;van Os et al, 1996), and has been shown to be reliable for follow-up assessments and adaptable across cultures (Jablensky et al, 1992, Susser et al, 2000.…”
Section: Measures At 4-year Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…We used this measure at the end of the follow-up period to obtain standardised retrospective assessments of patients' experiences, clinical and social outcomes for the entire period of illness operationalised as the period from the first contact with mental health services for FEP to the date of the last assessment recorded in electronic notes. The LCS measure has been widely used in prospective and retrospective studies (Ajnakina et al, 2017;Morgan et al, 2014;Schoeler et al, 2017;van Os et al, 1996), and has been shown to be reliable for follow-up assessments and adaptable across cultures (Jablensky et al, 1992, Susser et al, 2000.…”
Section: Measures At 4-year Follow-upmentioning
confidence: 99%
“…Similar to previous research (Morgan et al, 2014) using information extracted from clinical records, first remission was operationalised as the very first continuous period of ≥6 months of a complete absence of a clear record of psychotic symptoms in clinical notes, including no evidence of re-emergence of psychotic symptoms, re-admission to psychiatric wards, and/or having been re-referred to acute home treatment/crisis intervention services during the follow-up period (Ajnakina et al, 2017). This definition did not depend on whether non-psychotic symptoms (e.g.…”
Section: Clinical Assessment At Follow-upmentioning
confidence: 99%
“…Early experiences of psychosis often occur during adolescence to early adulthood, which irrespective of illness course can lead to persistent social disadvantage [2], so that close relationships, socializing with others, and employment can be difficult to maintain [2,[3][4][5]. Approximately 23% [2] to one third of people with psychotic disorders [1] also experience ongoing symptoms and disability, typically leading to continued engagement with mental health services [1].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinical presentation is heterogeneous not only when comparing between different individuals but also depending on the illness stage, varying from positive symptoms (hallucinations, delusions, disturbances of self, thought disorders, psychomotor abnormalities) to negative, affective and cognitive symptoms [5]. There is also considerable diversity in outcome: 35 to 65% of patients show an undulating course (i.e., episodic and neither continuous nor episodic) with good outcome and 12% to 32% present a chronic course with poor outcome [6]. Antipsychotic drugs are the mainstay of treatment for psychosis, yet there is considerable heterogeneity in their therapeutic efficacy [7,8].…”
Section: Introductionmentioning
confidence: 99%